Take it or leave it: (Non-) take-up behavior of social assistance in Germany - Hilke Kayser; Joachim R. Frick (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
Analyzing the under-consumption of benefits in the German means-tested Social Assistance program using data from the German Socio-Economic Panel Study we estimate a high non-take-up rate of more than 60 percent. We find distinct differences across population groups and significant impacts of factors such as stigma, application costs and social ties. Specifically, we show that the rate varies greatly depending on the determination of eligibility. Results pertaining to the amount of unclaimed benefits are qualitatively similar to those for the non-take-up rate. As expected, the proportion of outstanding benefits that is not claimed by eligible households is lower than the non-take-up rate because small entitlement amounts are more likely to remain unclaimed. In light of likely measurement errors in income and in our simulation of household needs, we provide a range of estimates yielding useful boundaries for the non-take-up rate. – – Basierend auf den Mikro-Daten des Sozio-oekonomischen Panels untersuchen wir Determinanten der Nichtinanspruchnahme von Sozialhilfe in Deutschland. Die Schätzung einer Nichtinanspruchnahmequote ("Dunkelziffer") von über 60 Prozent zeigt deutliche Unterschiede für verschiedene Bevölkerungsgruppen und zudem signifikante Einflüb e von Indikatoren zur Messung von Stigma, Kosten der Antragstellung und sozialen Bindungen. Resultate für die Höhe der nicht in Anspruch genommenen Sozialhilfebeträge sind qualitativ ähnlich. Wie erwartet ist die Rate der nicht ausgezahlten Sozialhilfeleistungen jedoch geringer als im Falle der Nichtinanspruchnahmequote, da es eher geringe Sozialhilfebeträge sind, die nicht beantragt werden. Darüber hinaus wird deutlich, wie stark die Berechnung der Inanspruchnahmequote mit der Bestimmung der Inanspruchnahmeberechtigung variiert. Angesichts der hohen Wahrscheinlichkeit von Messfehlern sowohl in den faktisch erhobenen Einkommensdaten als auch bei der Simulation des Bedarfseinkommens, bieten wir eine Reihe von Schätzungswerten und somit nützliche Sensitivitätsanalysen für die Nichtinanspruchnahmequote an.
Keywords: 330; Sozialhilfe; Sozialhilfeempfänger; Schätzung; Deutschland